Reflexões acerca da competitividade das redes comerciais judaico-portuguesas no século XVII - Jorun Poettering (Ler História, 2014)
The trade networks of the Portuguese Jews are usually considered to have been particularly extensive, dynamic and successful. Because of their common ethnic and religious background Portuguese Jews and New Christians are supposed to have shared a special commitment and solidarity towards each other benefiting their business. However, there are several arguments to challenge this assertion, indicating, on the contrary, that the Portuguese Jews had to overcome much greater impediments than the Christian merchants and that their trade networks were weaker.